2018
DOI: 10.1007/s00520-018-4293-z
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of implementing an electronic social support and resource visualization tool for caregivers in a neuro-oncology clinic

Abstract: clinicaltrials.gov, protocol number NCT03026699.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…[19][20][21] Several studies have evaluated the use of telehealth platforms for symptom monitoring, education and rehabilitation of people with brain tumours in a supervised clinic-based setting. [23][24][25][26][27][28][29] For example, in a mixed brain tumour sample, Erharter and colleagues 23 evaluated the implementation of computer-based symptom monitoring in the waiting room to alert physicians to changes in health. Most patients found the tablets easy to use and that administration time was acceptable, although nearly one third (30%) were unable to independently use the tablets due to functional impairment.…”
Section: -17mentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21] Several studies have evaluated the use of telehealth platforms for symptom monitoring, education and rehabilitation of people with brain tumours in a supervised clinic-based setting. [23][24][25][26][27][28][29] For example, in a mixed brain tumour sample, Erharter and colleagues 23 evaluated the implementation of computer-based symptom monitoring in the waiting room to alert physicians to changes in health. Most patients found the tablets easy to use and that administration time was acceptable, although nearly one third (30%) were unable to independently use the tablets due to functional impairment.…”
Section: -17mentioning
confidence: 99%
“…Several studies have evaluated the use of telehealth platforms for symptom monitoring, education and rehabilitation of people with brain tumours in a supervised clinic‐based setting 23–29 . For example, in a mixed brain tumour sample, Erharter and colleagues 23 evaluated the implementation of computer‐based symptom monitoring in the waiting room to alert physicians to changes in health.…”
Section: Introductionmentioning
confidence: 99%
“…The reviewed articles consisted of titles, abstracts, and full-text articles in English from 2010 to 2020, resulting in 10,078 records. The key articles included in the review are listed in Multimedia Appendix 1 [ 19 , 27 , 31 - 34 , 45 , 64 - 101 ]. A total of 45 articles met the eligibility criteria ( Multimedia Appendix 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that, although the application of technology-based interventions is on the rise, the term is seldom defined when applied in cancer research or practice. A review of the literature [31][32][33][34] shows that alarmingly, much of the research on technology-based interventions for patients with cancer fails to provide a clear definition of the term to shed light on key questions: (1) [35][36][37]. As one scholar, the prominent British physicist and mathematician Lord William Thomson Kelvin, succinctly put it, "What is not defined cannot be measured.…”
Section: The Importance Of Conceptual Claritymentioning
confidence: 99%
“…While previous research has shown positive outcomes associated with eSNAP [ 13 , 14 ], additional tailoring and engagement were needed. Thus, we developed a caregiver navigation component to complement and augment the eSNAP intervention, based on theory, existing patient navigation interventions, and stakeholder feedback.…”
Section: Introductionmentioning
confidence: 99%